2000
DOI: 10.1080/080352500456714
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, laboratory findings and differential diagnosis of benign acute childhood myositis

Abstract: In a retrospective study of 75 children with spastic cerebral palsy (CP), brainstem auditory evoked potentials (BAEP) were recorded and subsequently correlated with birthweight, gestational age, aetiology and type of CP, neuroradiological findings, additional impairments and disabilities (including the inability to walk independently). Seventeen patients (22.7%) had abnormal BAEP recordings. Thirteen of these 17 patients (76.5%) had spastic tetraplegia, 16 patients (94.1%) were full-term infants, 12 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 0 publications
3
45
0
5
Order By: Relevance
“…Benign acute childhood myositis is a condition which is characterized by sudden calf pain, inability to walk or difficulty in walking occuring after a prodromal period of 1-5 days following a viral upper respiratory disease and which resolves spontaneously (3). Previous studies reported the prodromal period to range between 2 and 31 days (1)(2)(3)(4)(5)10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benign acute childhood myositis is a condition which is characterized by sudden calf pain, inability to walk or difficulty in walking occuring after a prodromal period of 1-5 days following a viral upper respiratory disease and which resolves spontaneously (3). Previous studies reported the prodromal period to range between 2 and 31 days (1)(2)(3)(4)(5)10).…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in boys more frequently. The typical laboratory finding is high serum creatinine phosphokinase (CPK) level (2,3). Differential diagnosis with Guillain-Barre syndrome (GBS) which leads to difficulty to walk and with more severe diseases which proceed with myoglobinuria is important (3).…”
Section: Introductionmentioning
confidence: 99%
“…There are several typical skin conditions that can cause similar clinical findings in children, such as dermatomyositis, which presents with a progressive bilateral proximal muscle weakness, an increased CPK level, EMG changes, unusual muscle biopsy findings, edema, and purplish color change in the eyelids [6]. For the diagnosis of BACM, the most typical diagnostic finding is an increased CPK level in the serum [3]. Moderate degree CPK has been reported to range from 558 to 6800.…”
Section: Introductionmentioning
confidence: 99%
“…Usually developings due to post-infectious pathogens, myositis associated with rotaviruses is rarely reported [2]. A typical laboratory finding is a high level of serum keratin phosphokinase (CPK) [3]. Knowing detailed characteristics of benign acute childhood myositis will prevent unnecessary tests and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Benign childhood acute myositisis is a muscle syndrome that is most commonly seen after a viral infection [1]. The most common presentation of the disease is acute refusal to walk or altered gait during walking.…”
mentioning
confidence: 99%